2009
DOI: 10.3399/bjgp09x453990
|View full text |Cite
|
Sign up to set email alerts
|

How do common chronic conditions affect health-related quality of life?

Abstract: BackgroundComorbidity is common. National Institute for Health and Clinical Excellence (NICE) guidelines have been created to make best use of resources to improve patients' quality of life but do not currently take account of comorbidity. The effect of multiple chronic conditions with regard to health-related quality of life (HRQoL) is poorly researched. Criticisms of previous research have been due to patient-defined chronic conditions, lack of quantification of the effects of confounding factors, selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
123
5
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(146 citation statements)
references
References 28 publications
12
123
5
5
Order By: Relevance
“…The surveys included the EQ-5D: a generic QoL instrument covering the five dimensions of mobility, self-care, usual activities, pain/discomfort, and anxiety/depression, from which an index score is calculated. In the first study 16 a cross-sectional analysis showed how comorbidity affects the EQ-5D index. In the second study 17 the changes in the EQ-5D scores were calculated for patients who had three consecutive measurements over a 5-year period.…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…The surveys included the EQ-5D: a generic QoL instrument covering the five dimensions of mobility, self-care, usual activities, pain/discomfort, and anxiety/depression, from which an index score is calculated. In the first study 16 a cross-sectional analysis showed how comorbidity affects the EQ-5D index. In the second study 17 the changes in the EQ-5D scores were calculated for patients who had three consecutive measurements over a 5-year period.…”
Section: Quality Of Lifementioning
confidence: 99%
“…16,17 Both studies are based on postal surveys carried out in the registered population of two general practices. The surveys included the EQ-5D: a generic QoL instrument covering the five dimensions of mobility, self-care, usual activities, pain/discomfort, and anxiety/depression, from which an index score is calculated.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…COPD affects patients' functioning in daily life by reducing functional capacity and performance (Leidy, 1994) as well as quality of life (QoL) (Wang et al, 2008;Heyworth et al, 2009), due to dyspnoea, fatigue, cough, exacerbations, dietary problems, anxiety and depression (ATS/ERS, 2006;Miravitlles et al, 2007). Pulmonary rehabilitation (PR) in hospital settings for patients diagnosed with COPD has been found to increase functional capacity, QoL and decrease exacerbations (Lacasse et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular diseases such as myocardial infarction and heart failure impose a substantial burden on quality of life [1], though this can be improved significantly by prevention [2], rehabilitation [3] and other disease management strategies [4]. Moreover, many patients with cardiovascular disease may have other chronic conditions which will have an even more negative effect on quality of life [5], and women are reported to have worse HRQL than men. [6] Thus, it is not surprising that there has been a significant growth in the measurement of HRQL as a prime indicator of health outcome and therapeutic benefit in patients with cardiovascular disease [7][8][9][10][11][12][13].…”
mentioning
confidence: 99%